Introductory guide to the internet for Nanyang Business School. - Kao, Grace Sze Jwen. (2013)
In recent years, there have been trends suggesting the rapid growth of Internet usage in Singapore. As Singaporeans become more hard-pressed for time to spend on work, family and leisure, Internet services would gain in popularity and become widespread in the future. Internet is the world's largest internetwork of academic, research & development and commercial networks spanning the globe. There are more than four million computers on the Internet and an estimated fifty million Internet users world-wide, about 1.5 million of them in Asia. Until now, growth in the region has been restricted by underdeveloped telecommunications infrastructure and bureaucracies that have little concept of the technologies that they are trying to regulate.